Pharyngeal Flap versus Sphincter Pharyngoplasty for Hypernasality in Pediatric Patients: A Systematic Review of Postsurgical Outcomes - Ahmed, Nehad Jaser (Asian Journal of Pharmaceutics (AJP), 2025)
Velopharyngeal insufficiency (VPI) is a condition that impairs speech function and quality of life, often associated with cleft palate and other congenital or acquired conditions. Surgical management is the cornerstone of VPI treatment, with pharyngeal flap (PF), sphincter pharyngoplasty (SP), and combined techniques as the primary interventions. However, significant variability exists in these approaches’ effectiveness, safety, and durability, necessitating a systematic evaluation to guide clinical decision-making. This systematic review aimed to compare the effectiveness and safety of PF, SP, and combined techniques in the surgical management of VPI, focusing on resolution rates, obstructive sleep apnea (OSA) incidence, and revision surgery requirements. A comprehensive search was conducted across PubMed and Cochrane Library databases from inception to January 2025. Studies were screened based on predefined inclusion and exclusion criteria. Data extraction focused on surgical outcomes, including VPI resolution rates, OSA incidence, revision surgery rates, and speech outcomes. Study quality was assessed using the Newcastle–Ottawa scale. Statistical analyses and graphical representations were employed to synthesize findings. A total of 14 studies encompassing 1,574 participants were included. Combined techniques demonstrated the highest VPI resolution rates (mean: 87.2%), followed by PF (78.5%) and SP (65.8%). OSA incidence was highest for PF (12.3%), moderate for combined techniques (7.2%), and lowest for SP (5.6%). Revision surgery rates were significantly lower for combined techniques (10.3%) compared to PF (20.1%) and SP (18.5%). Meta-analytical trends revealed that combined techniques provided a significant relative risk (RR) reduction in OSA compared to PF (RR = 0.59, 95% confidence interval: 0.43–0.81, P = 0.002). Patient-specific factors, such as syndromic conditions and pre-operative anatomy, influenced outcomes across all techniques. This systematic review highlights the nuanced trade-offs between effectiveness and safety in the surgical management of VPI. Combined techniques emerged as the most effective and durable option, balancing high VPI resolution rates with moderate complication risks. PFs and SP remain valuable alternatives for specific patient profiles. Tailored surgical approaches and long-term post-operative monitoring are essential to optimize outcomes and minimize risks. These findings provide a robust evidence base for clinical decision-making and future research.